Pengaruh Ethical Climate, Personal Cost Dan Pemberian Financial Reward Terhadap Niat Melakukan Whistleblowing - Silfia Reshie; Henri Agustin; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to examine the influence of ethical climate, personal cost and the provision of financial rewards on whistleblowing intention. This research is quantitative research. The population in this study were employees of PT. Pegadaian (Persero) Padang Area. The sample in this study was taken using purposive sampling, namely 37 samples. The data collection method used is a survey method in the form of a questionnaire which was delivered directly to each Pegadaian Branch Unit. Data processing performed using SPSS. The results of this research indicate that ethical climate-egoism does not have a significant negative effect on whistleblowing intentions (sign 0.512). Ethical climate-benevolence does not have a significant negative effect on whistleblowing intentions (sign 0.284). Personal cost does not have a significant positive effect on the intention to do whistleblowing (sign 0.054) Ethical climate-principle has a significant positive effect on the whistleblowing intention (sign 0.047). Giving financial reward has a significant positive effect on whistleblowing intention (sign 0.009).